2017
DOI: 10.1053/j.gastro.2017.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anticoagulants in Patients With Cirrhosis and Portal Vein Thrombosis: A Systematic Review and Meta-analysis

Abstract: Based on a systematic review and meta-analysis, patients with cirrhosis and PVT who receive anticoagulant therapy have increased recanalization and reduced progression of thrombosis, compared with patients who do not receive anticoagulants, with no excess of major and minor bleedings and less incidence of variceal bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
298
3
10

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(328 citation statements)
references
References 24 publications
17
298
3
10
Order By: Relevance
“…Low molecular weight heparin has already been shown to be safe in patients with cirrhosis not admitted to invasive procedures . We demonstrate the safety of LMWH also in patients otherwise considered at high risk of bleeding for both the endoscopic procedure (ie, EVL) and the underlying disease (ie cirrhosis further complicated by PVT).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Low molecular weight heparin has already been shown to be safe in patients with cirrhosis not admitted to invasive procedures . We demonstrate the safety of LMWH also in patients otherwise considered at high risk of bleeding for both the endoscopic procedure (ie, EVL) and the underlying disease (ie cirrhosis further complicated by PVT).…”
Section: Discussionmentioning
confidence: 62%
“…We demonstrate the safety of LMWH also in patients otherwise considered at high risk of bleeding for both the endoscopic procedure (ie, EVL) and the underlying disease (ie cirrhosis further complicated by PVT). Although PVT increases the risk of variceal bleeding in cirrhotic patients and anticoagulation is indicated as its first line treatment, no clear‐cut indication has been provided on the opportunity of performing prophylactic EVL as a concomitant treatment to avoid variceal bleeding . A recent study has shown prophylactic treatment with TIPS as more effective than EVL plus non‐selective betablockers and warfarin for the prevention of rebleeding in patients with non‐cavernomatosus PVT .…”
Section: Discussionmentioning
confidence: 99%
“…Historically, thrombocytopenia and abnormal coagulation tests in cirrhosis have been perceived as a reflection of bleeding risk. However, a recent systematic review and meta‐analysis of anticoagulation in cirrhotic patients with portal vein thrombosis, therapeutic anticoagulation was not associated with major or minor bleeding with some studies even reporting lower rates of spontaneous variceal bleeding . Evidence also suggests that a hypercoagulable state persists in cirrhotic patients with thrombocytopenia, at least in part, due to a process in which lipopolysaccharide‐induced platelet sensitisation results in enhanced in vivo platelet activation .…”
Section: Discussionmentioning
confidence: 99%
“…The most recent systematic review including meta‐analyses of recanalization and the progression of PVT in patients with cirrhosis comparing the effects of anticoagulation therapy to no therapy included eight studies with 353 patients . This study showed that portal vein recanalization was more frequent with anticoagulation than without (complete or partial 71% vs 42%, complete 53% vs 33%, respectively, P < .0001), and that progression was less common (9% vs 33%, respectively, P < .0001).…”
Section: Recanalization Of the Thrombosed Portal Veinmentioning
confidence: 98%